KONSENSUS ANTARA PEMERINTAH, PERUSAHAAN, DAN PEKERJA DALAM MASALAH KETENEGAKERJAAN - Geovani Meiwanda (Jurnal Kebijakan Publik, 2018)
Konsesensus antara Pemerintah, Perusahaan, dan Pekerja dalam MasalahKetenagakerjaan. Development conducted by the government leads to achievements in welfare,welfare can not be separated from three main aspects in support of the economy, education andhealth. The welfare that a country achieves from the economic aspect can not be separated frommacroeconomic policies, investment growth that will lead to industrial and labor policy. Indonesiaseeks to increase incoming investment, then the country’s economic growth will be better so thatthe welfare of Indonesia increases. This article will analyze the investment in Indonesia, notaccompanied by the welfare of workers within a company, there is a consensus within thegovernment, the company and workers. The legal product protecting the industry and employmentin Indonesia is not present, the profit that is only given to the owner of the company not to thestate, whose essence should be when the investment entering the country is ready to presentintervention, and protect for the benefit of the welfare of the workers.